2018
DOI: 10.20538/1682-0363-2018-4-54-64
|View full text |Cite
|
Sign up to set email alerts
|

Morphophenotypic predictor of the development of visceral obesity in patients with schizophrenia receiving antipsychotic therapy

Abstract: Objective:revealing the role of morphophenotypic indices in the development of visceral obesity in patients with schizophrenia receiving quetiapine and risperidone therapy.Materials and methods.56 indoor patients with schizophrenia who received quetiapine (n= 23) or risperidone (n= 33) at medium doses were examined. Included persons were from 18 to 65 years old with at least a 1 year history of disease, the condition of which met the criteria of schizophrenia according to ICD-10. The Basis map of sociodemograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
1
0
1
Order By: Relevance
“…This fits into the differences in approaches to antipsychotic therapy between hospitals discussed above and the general pattern of the formation of MetS, revealed in many studies, in particular, a large systematic review found that in patients with severe mental illness, a higher BMI was associated with lower levels of physical activity as a consequence of the lack of resources or professional support (44). Our previous study also showed the role of the bone component of body composition in the formation of MetS (45).…”
Section: Anthropometric Parameterssupporting
confidence: 72%
“…This fits into the differences in approaches to antipsychotic therapy between hospitals discussed above and the general pattern of the formation of MetS, revealed in many studies, in particular, a large systematic review found that in patients with severe mental illness, a higher BMI was associated with lower levels of physical activity as a consequence of the lack of resources or professional support (44). Our previous study also showed the role of the bone component of body composition in the formation of MetS (45).…”
Section: Anthropometric Parameterssupporting
confidence: 72%
“…It is important to control abdominal (including visceral) obesity, dyslipidemia, and increased glucose as components of the MetS already at the beginning of antipsychotic therapy. Visceral obesity occurs in 40-60% of schizophrenia patients and the accumulation of large amounts of abdominal and pericardial fat has considerable endocrine and cardiovascular consequences and negatively influences the health in general as well [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Согласно данным метаанализа, включающего более 25 000 пациентов с шизофренией, распространенность МС составила 32,5% [10]. Рассматривается возможность использования индекса Таннера (Tanner) в качестве прогностического фактора развития висцерального ожирения у больных шизофренией, получающих кветиапин [11].…”
Section: Introductionunclassified